Profile of Serum Creatinine Levels with Creatinine Clearance Test (CCT) of Patients with Type 2 Diabetes Mellitus at Budhi Asih Hospital in 2021 - Prasetyorini, Tri; Lestari, Diah; Anzalinna, Aliffiya; Suratun, Suratun (jitek, 2022)
Diabetes Mellitus (DM) is a group of metabolic diseases with hyperglycemia characteristics that can lead to kidney complications. One of them is Diabetic Nephropathy which is a complication of microvascular damage and its monitoring is done by checking serum creatinine and creatinine clearance test (CCT). The purpose of this study was to determine the relationship between serum creatinine levels and creatinine clearance test (CCT) in patients with type 2 DM. Perform a serum creatinine examination which is used as the basis for calculating CCT. From 53 data on type 2 DM patients who had high serum creatinine levels, 49 (92.5%) people, 51 (96.2%) people with low CCT levels. The results of Spearman's correlation statistical test showed a correlation between serum creatinine levels and CCT. The strength of the correlation is moderate, and the correlation shows a negative direction with a correlation coefficient (r) of -0.389. It can be concluded that the higher the serum creatinine level, the lower the CCT value, so DM patients must control blood glucose regularly in order to prevent a decrease in kidney function that can lead to complications.